THOLE, H. Inventory of documents - THOLE, H. (ARCA, 2018)
MPC for constituency Weenen, Natal; Member of the Grey Shirts Movement; Farmer, Greytown district; Documents pertaining to Grey Shirts Movement
Keywords: THOLE, H.; Grey Shirts Movement; Inventories; Politicians; National Party